Design and control of the nonholonomic manipulator - Nakamura, Y; Chung, W; Sordalen, OJ (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2001)
Nonholonomic constraints are exploited to design a controllable eta -joint manipulator with only two inputs. Gears subject to nonholonomic constraints are designed to transmit velocities from the inputs to the passive joints, The system possesses a triangular structure for which a conversion into chained form is presented, The nonholonomic manipulator can, therefore, be controlled with an open loop or a closed loop using existing controllers for chained form, Mechanical design is established, and experimental results proved the usefulness of design of the nonholonomic manipulator and applied control schemes. While previous publications have assumed that the nonholonomic systems are given and have developed theory for these systems, this paper points out a new direction where the nonholonomic theory is used to design controllable and stabilizable systems.
Keywords: EXPONENTIAL STABILIZATION; SYSTEMS; ROBOTS; MOTION